Proceedings of 1993 Winter Simulation Conference - (WSC '93)
DOI: 10.1109/wsc.1993.718044
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Slam II/sup R/ and Slamsystem/sup R/

Abstract: SLAM 11 is a general-purpose language which has been used since 1979 to model a wide variety of systems: manufacturing operations, transportation systems, communication networks, computer systems, military operations and material handling systems, just to name a few. Experience with these applications, plus development in simulation research, have led to the expansion of the language throughout its lifetime. The ease of using the SLAM I1 language was greatly increased by the introduction of SLAMSYSTEM in 1988;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…A nearly four-fold difference exists in the free fraction of warfarin in human and dog plasmas when determined by ultrafiltration (Bachmann, 1974). This difference is in good agreement with the relative differences in warfarin binding constants for human and dog albumin (O'Reilly, 1970), and may contribute to the shorter plasma half-life and apparently greater sensitivity of the dog to the hypoprothrombinaemic effect of warfarin compared to man. The normal value for the free warfarin fraction over the therapeutic range of warfarin plasma concentration in man is 0.6.x This value can be increased to 1.0% with relatively small concentrations of phenylbutazone (40 pg ml-l) (Bachmann, 1974).…”
Section: Discussionsupporting
confidence: 61%
“…A nearly four-fold difference exists in the free fraction of warfarin in human and dog plasmas when determined by ultrafiltration (Bachmann, 1974). This difference is in good agreement with the relative differences in warfarin binding constants for human and dog albumin (O'Reilly, 1970), and may contribute to the shorter plasma half-life and apparently greater sensitivity of the dog to the hypoprothrombinaemic effect of warfarin compared to man. The normal value for the free warfarin fraction over the therapeutic range of warfarin plasma concentration in man is 0.6.x This value can be increased to 1.0% with relatively small concentrations of phenylbutazone (40 pg ml-l) (Bachmann, 1974).…”
Section: Discussionsupporting
confidence: 61%
“…In the present investigation, the binding behavior of the isomers with human serum albumin was characterized by equilibrium dialysis to determine if there is a correlation between the free fraction of the isomers in uitro and clinically observed elimination kinetics. In two studies (9, lo), the S(-)-isomer had a significantly higher affinity for the primary site; in two other studies (11,12), no significant differences in isomer binding were found.…”
mentioning
confidence: 90%
“…There is n good deal of variation between different workers on supposedly similar systems, and inspection of the data suggested that choice of treatment could be responsible in part. For example, consider the bishydroxycoumarin-human plasma albumin interaction where Chignell(l970) reported the number of sites in the highest affinity class (n3 as 3 and an association constant (K,) of 7.7 x lo5 M-,; Garten & Wosilait (1971) found n, = 2.08 and K, = 2.08 x lo6 M -~; O'Reilly (1971) gave n, = 2-0 f 0.1 and K , = 2.31 3 0.05 x lo5 M-, and Cho, Mitchell & Pernarowski (1971) gave n, = 3 and K , = 3.5 x 105 M-1.…”
mentioning
confidence: 99%